Uranium Budget and Leaching in Swiss Agricultural Systems - Bigalke, Moritz; Imseng, Martin; Schneider, Stephan; Schwab, Lorenz; Wiggenhauser, Matthias; Keller, Armin; Müller, Michael; Frossard, Emmanuel; Wilcke, Wolfgang (Frontiers in Environmental Science, 2020)
Many mineral P fertilizers contain toxic uranium (U) in high concentrations. When the fertilizers are applied to agricultural sites, U can either accumulate in the soil or leach to ground and surface waters. We analyzed the U fluxes at three arable and three grassland agricultural sites on the Swiss plateau for 1 year. We calculated all inputs and outputs to the soils, modeled the speciation of U in the soil solution and investigated the possible leaching of U along preferential flow paths. We found that all sites showed positive U budgets (+0.9–6.6 g ha–1 y–1), indicating an accumulation of U. However, the accumulation of U was low and a doubling of U concentration in the surface soil would need 850–2,660 years assuming today’s U fluxes. Mineral P fertilizers were the quantitatively most important input, followed by manure application and mineral weathering (only important in the soils developed on limestone). While at sites with slightly acidic pH only little U (<0.01 μg L–1) was leached, the U leaching increased at neutral pH values, because of the formation of carbonato-U complexes. In all soil solutions, the U concentrations (≤0.8 μg L–1) were below legal threshold values and comparable to local drinking and surface waters. We found no indication for enhanced U leaching along preferential flow paths.